ECOLOGICAL GROUPING OF PHYTONEMATODES OF TUGAI PLANTS (ResearchJet Journal of Analysis and Inventions, 2021)
Phytonematodes usually affect plants of various ages, but they are dangerous for woody plants in the first years of life. When plants are infected with phytohelminths, growth retardation, deformation of stems and shoots, wilting of shoots, chlorosis are observed. The study of phytonematodes, their types and conditions of development and conditions of adaptation, is relevant.